The utopia of transparency - Alves, Artur Matos (Teorija in praksa, 2019)
This article introduces the concept of "platform humanism" to examine the discourse on communicative transparency and social accountability adopted by online intermediaries and service providers. By critically analysing Facebook's adoption of humanistic themes in the context of its corporate communications along with more opaque social responsibility practices, this article intends to provide empirical and critical insights into the political economy of online platforms. It identifies the transparency discourse as a key ideological element of the digital platform economy, characterises Facebook's transparency discourse as being outwardly dominated by a humanistic communitarian terminology, while relying heavily on quantification, arguments for self-regulation, and implied consent practices.
Keywords: Analiza diskurza; Communication; Discourse analysis; Facebook; Facebook (Electronic resource); informacijska tehnologija; Internet service providers; Komunikacije; Ponudniki internetnih storitev; transparentnost